COVID-19 and the other pandemic: populations made vulnerable by systemic inequity - Gray, Darrell M. (Nat Rev Gastroenterol Hepatol, 2020)
Greater than the coronavirus disease 2019 (COVID-19) crisis, systemic inequity in social determinants of health is the pandemic that has long fostered vulnerability to disease and poor health outcomes in the USA. Our response has major implications for the health of our nations.